Ethnographic lens: Understanding managerial and operational level perspectives on ESP teachers roles - Poedjiastutie, Dwi; Masduki; Mayaputri, Velmi (Asian Journal of Education and Training, 2024)
This study investigates the managerial level (the deans of the faculties and the director of ESP) perspectives and ESP teachers’ perspectives (operational level) on how they assume their roles in teaching ESP. This study used an ethnographic approach. The phenomena of an ethnography are commonly examined from a collective perspective. This suggests analyzing the culture under investigation from an insider’s viewpoint by emphasizing the significance that the members of that society attribute to it. The findings show that sociocultural factors are assumed to influence the deans’ expectations of what teachers must do in comparison to what teachers themselves should be doing. ESP teachers at the operational level assume their roles in teaching and learning ESP as motivation builders, classroom controllers, teaching strategy innovators and lifelong learners. Meanwhile, the deans of the faculty’s (managerial level) expectations of ESP teacher roles entail a material developer, a curriculum contributor, a language trainer, a student mental safeguarding, a collaborator and a program evaluator. While deans and teachers share a common goal of educating students, their roles, responsibilities and perspectives differ significantly leading to different expectations. Both cohorts namely managerial level and ESP teachers should intensively discuss to obtain a satisfactory agreement in executing roles and responsibilities. Besides, when designing professional development, it is suggested to focus on two areas: enhancing and sustaining instructors’ English proficiency and expanding language teaching knowledge and skills.